Phage SEP1 hijacks Staphylococcus epidermidis stationary cells metabolism to replicate - Silva, Maria Daniela (2024)
In nature, bacteria often survive in a stationary state with low metabolic activity. Phages use the metabolic machinery of the host cell to replicate, and, therefore, their efficacy against non-dividing cells is usually limited. Nevertheless, it was previously shown that the Staphylococcus epidermidis phage SEP1 has the remarkable capacity to actively replicate in stationary-phase cells, reducing their numbers. Here, we studied for the first time the transcriptomic profiles of both exponential and stationary cells infected with SEP1 phage using RNA-seq to gain a better understanding of this rare phenomenon. We showed that SEP1 successfully takes over the transcriptional apparatus of both exponential and stationary cells. Infection was, however, delayed in stationary cells, with genes within the gp142-gp154 module putatively implicated in host takeover. S. epidermidis responded to SEP1 infection by upregulating three genes involved in a DNA modification system, with this being observed already 5 min after infection in exponential cells and later in stationary cells. In stationary cells, a significant number of genes involved in translation and RNA metabolic and biosynthetic processes were upregulated after 15 and 30 min of SEP1 infection in comparison with the uninfected control, showing that SEP1 activates metabolic and biosynthetic pathways necessary to its successful replication.